Comparação da eficácia e segurança do laser cirúrgico de diodo com o eletrocautério no tratamento da hiperplasia fibrosa inflamatória - Alessandro Oliveira de Jesus (2018)
Efficacy and safety comparison of diode surgical laser with electrocautery in the treatment of inflammatory fibrous hyperplasia Inflammatory fibrous hyperplasia (IFH) is a common lesion in the oral cavity, which affects approximately 5 to 16.7% of individuals who wearing prosthesis. It is a lesion characterized by low-grade chronic irritation due to ill-fitting prostheses. The main treatment of IFH is the removal of the causal factor that allows regression of the lesion and sometimes is necessary the association with surgical excision. Surgical treatment could be using scalpel, cryotherapy, electrocautery or surgical laser. The aim of the present study was to evaluate and compare, through a randomized tripleblind clinical trial, the safety and the efficacy of surgical techniques using electrocautery and diode laser in the treatment of IFH. It was evaluated the peroperative clinical parameters: the number of anesthetic tubes used, bleeding, deposited tissue energy, energetic energetic flow, time of incision and superficial thermal variation tissue, and the post operative parameters: pain, use of analgesic, development of swelling, chewing difficulty, speaking difficulty, wound healing area, for a period of 28 days post-operatively. The individuals were divided into two groups: surgical treatment with diode laser with wavelength of 808 nm and with electrocautery. A total of 36 patients were included in the study, 18 in each group. No significant differences were found in the evaluation of per and postoperative clinical parameters for the removal of IFH using laser or electrocautery. Thus, it is possible to affirm that both surgical techniques are effective and safe for the treatment of IFH in the same proportion.